Transformasi Pendidikan Pesantren dalam Pembentukan Karakter Anak Asuh di LKSA Budi Mulia Gurah pada Era Society 5.0 - Moh. Sholeh; Dhanang Amoasidhi; Ahmad Zubairi (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2024)
Technology development in the era of Society 5.0 affects various aspects, including Islamic boarding school education, known for its traditional approach based on Islamic values. The main challenge for Islamic boarding schools, especially in the Child Welfare Institution (LKSA), is utilizing technology without eliminating the essence of character education. This study examines how Islamic boarding schools in LKSA can adopt technology to shape the character of foster children while maintaining traditional Islamic values. Using a descriptive qualitative approach with a case study design, data were obtained through in-depth interviews, participatory observation, and document analysis. The study results indicate that integrating technology in Islamic boarding school education faces challenges in terms of infrastructure and human resource readiness. However, technology can improve the quality of learning if used carefully so as not to sacrifice traditional values. This study highlights the importance of balancing modernization and tradition in the digital era. It suggests the need for the right strategy so that Islamic boarding schools can optimally utilize technology to improve students' character education. This study is expected to provide insight into the development of Islamic boarding school education in the increasingly complex era of Society 5.0.